Trends in ergonomics/human factors V - International Industrial Ergonomics and Safety Conference (3rd : 1988 : New Orleans, La.); Aghazadeh, Fereydoun (Amsterdam ; New York : North-Holland ; New York, NY : Sole distributors for the U.S.A. and Canada, Elsevier Science Pub Co, 1988)
163940